FACTORS THAT INFLUENCE THE RETURN OF STOCK PROPERTY COMPANIES LISTED IN INDONESIA STOCK EXCHANGE 2016-2019 - Kusno, Ayu Hafizha; Haryanto, Mulyo (Faculty of Economics and Business Diponegoro University, 2020)
This study aims to analyze the factors that influence stock returns of the property sector in the Indonesia stock exchange period 2016-2019. The population used in this study is 23 companies in the real estate property sector. The sample chosen uses a purposive sampling technique on secondary data obtained from the IDX website and the official website of Bank Indonesia. The analysis technique used is multiple regression analysis using SPSS version 24. The results obtained indicate that only the interest rate and exchange rate variables have a significant effect on the stock returns of property sector companies listed on the Indonesia Stock Exchange in 2016-2019. Furthermore, the variable studied only affects the stock returns of the property sector in the Indonesian stock exchange in 2016- 2019 by 6.1%. This proves that the anomalous phenomenon occurs in the data of property and real estate companies in Indonesia